Potential biomarkers on gametogenesis process and in sperm quality of european EEL (Anguilla anguilla) - Leonardo, Ana Margarida Assis (2015)
Dissertação de mestrado, Aquacultura, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015 The over-exploitation of European eel (Anguilla anguilla) has been damaging natural stocks of wild populations, creating the need of improvement in the captive breeding techniques. A better understanding of the reproductive cycle of the European eel is necessary, in order to create independence from natural environment. In the present study, the sexual maturation of male eels was induced by human chronic gonadotropin (hCG), with the purpose of sexually mature eel males in captivity. Biomarkers were used to check the quality of fresh and cryopreserved sperm. Computer-assisted sperm analysis (CASA) was used to analyze the quality parameters of sperm. Tests as the Luminometric Methylation Assay (LUMA) and analysis of the progestin receptors (2 nuclear and 5 membrane receptors), using the polymerase chain reaction (qPCR), were conducted to verify the capability of these analyses, to become new markers of quality, both for the sperm and gametogenesis process. It was found that the methylation using LUMA techniques revealed not to be a good biomarker of sperm quality of European eel. Also, 3 of the expressed receptors (mPRalpha, mPRAL1 and mPRAL2) are potential molecular markers of sperm quality and gametogenesis due to their expression profile on the testis. With these tools is expected to help the development of aquaculture industry of European eel. A exploração excessiva de enguia Europeia (Anguilla anguilla) tem vindo a danificar os stocks naturais das populações selvagens, criando a necessidade de melhorar as de técnicas de reprodução em cativeiro. Visto que todas as enguias criadas em cativeiro são originárias do meio natural. Uma melhor compreensão do ciclo de reprodução da enguia Europeia é necessária, para deste modo se criar a independência da indústria do meio natural. No presente estudo, a maturação sexual de enguias macho foi induzida através da gonadotrofina crónica humana (hCG), com a finalidade ...